Sustainable energy consumption and production: A case study for Eco-enerhiya Renewables Inc. - Mendoza, Trisha Anne S.L. (Animo Repository, 2010)
The pivotal aim of the study is to determine what factors will ensure the sustainability of using RE resources like coco-biomass for energy generation. The researcher has chosen to use ERI as its case study by using the Integral framework analysis, which is used in understanding factors: behavioral, psychological, cultural and system that affect Quezon farmers, what influences decisions in ERIs value chain and the instruments used towards sustainable initiatives. The Marrakech process was used alongside the previous framework in the analysis, which is a multi-stakeholder process that primarily involves the Philippine government agency programmes. The researcher believes that the introduction of the Marrakech framework supports the implementation and monitoring towards sustainable consumption and production and more importantly towards an environmentally sustainable direction. In light with energy being the crucial sector in the Philippines, the researcher supports the need for the Philippine government to institutionalize SCP as a pre-condition to set the right attitude and ensure strength and responsibility among government agencies. The researcher recommends ERI to take the first step in adopting the Marrakech process, which will spur the creation of policies and tools towards a RE efficient system, raw material sustainability in this case, coco-biomass and sustainable employment for the farmers of Quezon.